2016
DOI: 10.1016/j.btre.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities of fish protein hydrolysates from defatted salmon backbones

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 43 publications
8
53
0
4
Order By: Relevance
“…Papain has previously been reported to be capable of producing bioactive peptides from fish protein hydrolysates. 28,29 Moreover, this result is in accordance with the study by Abdulazeez et al, 30 who also reported the use of 10 mg mL −1 papain to digest narrow-barred Spanish mackerel (Scomberomorus commerson) and suggested that the derived protein hydrolysate was an ideal choice for use in biomedicine and commercial aspects. Thus the 10 mg mL −1 papain-derived SBPH was selected for further studies.…”
Section: Free Radical Scavenging Activities Of the Sbphssupporting
confidence: 90%
“…Papain has previously been reported to be capable of producing bioactive peptides from fish protein hydrolysates. 28,29 Moreover, this result is in accordance with the study by Abdulazeez et al, 30 who also reported the use of 10 mg mL −1 papain to digest narrow-barred Spanish mackerel (Scomberomorus commerson) and suggested that the derived protein hydrolysate was an ideal choice for use in biomedicine and commercial aspects. Thus the 10 mg mL −1 papain-derived SBPH was selected for further studies.…”
Section: Free Radical Scavenging Activities Of the Sbphssupporting
confidence: 90%
“…The hydrolysis was performed as described by Slizyte et al . (). Based on earlier experiments (Slizyte et al ., ), the following experimental set‐up was chosen.…”
Section: Methodsmentioning
confidence: 97%
“…The mixture of stick water and sediments were used as a raw material for hydrolysis. The hydrolysis was performed as described by Slizyte et al (2016). Based on earlier experiments (Slizyte et al, 2016), the following experimental set-up was chosen.…”
Section: Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Protein hydrolysates can be obtained from different animal sources and their by-products, such as fish viscera (Feltes et al, 2010;Roslan, Mustapa Kamal, Md. Yunos, & Abdullah, 2015;Roslan et al, 2014;Silva, Ribeiro, Silva, Cahú, & Bezerra, 2014); sardine viscera (Venturin et al, 2017); blue whiting (Micromesistius poutassou) (Harnedy et al, 2018); salmon backbone (Slizyte et al, 2016); bovine liver (Di Bernardini et al, 2011); porcine liver (Shimizu et al, 2006); swine tissues (Damgaard, Lametsch, & Otte, 2015); swine blood (Chang, Wu, & Chiang, 2007); chicken blood (Zheng, Si, Ahmad, Li, & Zhang, 2018); swine plasma (Liu, Kong, Xiong, & Xia, 2010); cattle plasma (Bah, Carne, McConnell, Mros, & Bekhit, 2016); shrimp viscera (Katsuwonus pelamis) (Klomklao & Benjakul, 2016); and boneless chicken carcasses (Oliveira, Franzen, Terra, & Kubota, 2015). For representing potentially inexpensive feedstocks, these by-products have become industrially relevant to the meat industry, which has come to invest in attractive technology solutions that are efficient and able to deliver products with high levels of protein and essential amino acids (FAO, 2017;Mora et al, 2014;Toldrá et al, 2016).…”
mentioning
confidence: 99%